Os conselhos escolares na efetivação da gestão democrática: alguns limites e possibilidades - Serafini, Rossonia Marini (2017)
This Master's dissertation has contributed to the implementation of democratic management through the strengthening of the School Councils, bringing some limits and possibilities found in this theme. It has as a research problem the following question: can the school council effectively characterize a Democratic Management in the context of the Institutions of Education? The general objective is to analyze the process of decentralization of power in order to democratize the management relations of the school through the performance of the school council in public schools. The methodology used was the qualitative research, type of study of multicasos, using questionnaires, documentary analysis and focus groups, having as a field of research schools of the public network of Santa Maria and as subjects the members of the School Councils. I present as a result of the research indications of the fragility of the school councils, having concluded, after tabulation of the research, been verified the lack of training of managers and counselors, which proves as the high point of this research that the public power is urgently needed together with the school institutions providing the training of all involved in this process of strengthening the School Councils, that is, every school community. The final product of this research was the construction of a protocol with suggestions of activities that were experienced in the school of application aiming at strengthening the school counseling.